EFFECTIVENESS OF RECIPROCAL PEER TUTORING AND MULTISYSTEMIC THERAPIES ON ADOLESCENTS OFFENDING BEHAVIOUR - Oyesoji Amos Aremu; Waliat Folasade Adeyemo; Stephen Oluwaseun Emmanuel (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
This study examined the impact of reciprocal peer tutoring and multisystemic therapy on reducing offending behaviour in out-of-school adolescents at motor parks in Ogun State, Nigeria. Focusing on peer influence and self-control as moderating variables, the research employed a multistage sampling technique to select participants from three motor parks across different senatorial districts. The study adopted a pre-test-post-test control group quasi-experimental design,with a 3x3x3 factorial matrix involving two experimental groups and one control group. A multistage sampling technique was employed to select 89 out-of-school adolescents from three major motor parks. The treatment lasted eight weeks in which the participants were randomly assigned into two experimental conditions (reciprocal peer tutoring and multisytremic), while the control group received no treatment. The findings revealed a significant main effect of the treatments on reduction of offending behaviour. The moderators, peer influence and self-control also significantly influenced the effectiveness of the treatment. It is concluded that reciprocal peer tutoring and multisystemic therapy are effective in the reduction of offending behaviour among out-of-school adolescents. Peer influence and self-control were also identified as effective.  These findings hold significant implications for counselling practice and policies as it relates to offending behaviour of out-of-school adolescents in Nigeria.